New Authorities of Social Media of the XXI Century - Bednarek, Józef (Pedagogical Discourse, 2012)
Creating an information society, and then a knowledge society and their challenges, create the need to shape new socio-media competences. Their importance and place in the context of new opportunities and threats of the latest digital media and interactive technologies is special. Recent challenges relate to the latest changes related to the threats of cyberspace and the virtual world. For this reason, these competences are extremely important and useful, not only for educators and teachers, but also for every human being. The development and use of digital media and information and communication technologies also influenced the largest transformations in education and human functioning. For this reason, new socio-media competences take on a new dimension and become the most important distinguishing feature of human activity and innovation.